2022
DOI: 10.1039/d1ee03046a
|View full text |Cite
|
Sign up to set email alerts
|

Water as a hole-predatory instrument to create metal nanoparticles on triple-conducting oxides

Abstract: Single-phase materials with mixed ionic and electronic conductivity underpin multiple solid-state electrochemical devices as promising electrodes. In particular, triple-conducting oxides that carry protons, oxygen ions, and electron holes simultaneously have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…During the last decade, considerable research efforts have been directed to the development of alternative cathodes for PCFCs. 17–19 Among them, perovskite-based electrodes have received the most attention because of their compositional flexibility and versatile properties. Various perovskite-type oxygen ion and electron co-conducting, and proton, oxygen ion and electron triple-conducting oxides have been exploited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, considerable research efforts have been directed to the development of alternative cathodes for PCFCs. 17–19 Among them, perovskite-based electrodes have received the most attention because of their compositional flexibility and versatile properties. Various perovskite-type oxygen ion and electron co-conducting, and proton, oxygen ion and electron triple-conducting oxides have been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, considerable research efforts have been directed to the development of alternative cathodes for PCFCs. [17][18][19] Among them, perovskite-based electrodes have received the most attention because of their compositional…”
Section: Introductionmentioning
confidence: 99%
“…The exsolution of transition metals in perovskite oxides (ABO 3 ) is considered as an intelligent catalyst design for energy applications. 22,23 It is oen observed that oxygen vacancies alter the surface segregation of the doping elements present in perovskite. SrTiO 3 , which is oen studied in defect chemistry, is the prototype of perovskite oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, PCECs can provide high electrochemical performance at intermediate to low working temperatures (450−650 °C). 2 Ba-based perovskite materials including BaCe 0.75 Y 0.15 O 3-δ (BCY), BaZr 0.85 Y 0.15 O 3-δ (BZY), and BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ (BZCY) have been used as electrolyte materials owing to their high proton conducting properties. 3−5 However, in the case of conventional sintering using heat convection, the poor sinterability nature of the protonic perovskite oxides inevitably requires high temperatures (>1500 °C) and long durations (up to ∼20 h) in the sintering process to achieve highly dense electrolyte structures (left side of Figure 1).…”
mentioning
confidence: 99%
“…Proton conduction (H + ) in oxides has a significantly lower activation energy (0.4–0.6 eV) than oxygen ion conduction (O 2– ). Hence, PCECs can provide high electrochemical performance at intermediate to low working temperatures (450–650 °C) …”
mentioning
confidence: 99%